Invenção de paisagens urbanas: atualizações do passado por meio da artedigital - Rosa, Simone Melo da (2014)
This research utilizes the manipulation of digital images to link past, present and future, besides pointing out the existing hybridization in ancient architectural blends with your existing urban context . The invention of urban landscapes combines images of cultural heritage ( photographed or painted ) with elements of urban visuality , inferring whether their memories , and memories subjectifications ; instigating the everyday diversity and acceleration has th. The poetic creation produced from this context is a way of suggesting possibilities for different interpretations , reached in the deconstruction of the urban landscape . This study tra -ering plastic creations that were becoming such production began with di - gitais prints and projected images sequences in plants and concluded with the creation of videos that mix footage and scanned images , in building invented landscapes . Later, such landscapes are presented in installations where partially overlapping images with the intention of exploring " instant hybridizations ." This study has two main operational concepts : invention as production of images , and hybridization , as the songwriting process . The various theoretical and practical pursuits resulted in " Inventions of Urban Landscapes " , invented urban spaces that highlight certain ancient architectures and highlight the diversity , indeterminacy , uncertainty , instability and hybridisation of the urban landscape that contains these buildings as a way to update the past. With this visual poetics proposed another way of perceiving and wondering about the old buildings in the city .